Cardiovascular events and target organ damage in primary aldosteronism compared with essential hypertension: a systematic review and meta-analysis. Issue 1 (January 2018) - Monticone, Silvia; D'Ascenzo, Fabrizio; Moretti, Claudio; Williams, Tracy Ann; Veglio, Franco; Gaita, Fiorenzo; Mulatero, Paolo
Summary: Background: There is conflicting evidence, relying on heterogeneous studies, as to whether aldosterone excess is responsible for an increased risk of cardiovascular and cerebrovascular complications in patients with primary aldosteronism. We aimed to assess the association between primary aldosteronism and adverse cardiac and cerebrovascular events, target organ damage, diabetes, and metabolic syndrome, compared with the association of essential hypertension and these cardiovascular and end organ events, by integrating results of previous studies. Methods: We did a meta-analysis of prospective and retrospective observational studies that compared patients with primary aldosteronism and essential hypertension, to analyse the association between primary aldosteronism and stroke, coronary artery disease (as co-primary endpoints), atrial fibrillation and heart failure, target organ damage, metabolic syndrome, and diabetes (as secondary endpoints). We searched MEDLINE and Cochrane Library for articles published up to Feb 28, 2017, with no start date restriction. Eligible studies compared patients with primary aldosteronism with patients with essential hypertension (as a control group) and reported on the clinical events or endpoints of interest. We also compared primary aldosteronism subtypes, aldosterone-producing adenoma, and bilateral adrenal hyperplasia. Findings: We identified 31 studies including 3838 patients with primary aldosteronism and 9284 patients with essential hypertension. After a median of 8·8 years (IQR 6·2–10·7) from the diagnosis of hypertension, compared with patients with essential hypertension, patients with primary aldosteronism had an increased risk of stroke (odds ratio [OR] 2·58, 95% CI 1·93–3·45), coronary artery disease (1·77, 1·10–2·83), atrial fibrillation (3·52, 2·06–5·99), and heart failure (2·05, 1·11–3·78). These results were consistent for patients with aldosterone-producing adenoma and bilateral adrenal hyperplasia, with no difference between these subgroups. Similarly, primary aldosteronism increased the risk of diabetes (OR 1·33, 95% CI 1·01–1·74), metabolic syndrome (1·53, 1·22–1·91), and left ventricular hypertrophy (2·29, 1·65–3·17). Interpretation: Diagnosing primary aldosteronism in the early stages of disease, with early initiation of specific treatment, is important because affected patients display an increased cardiovascular risk compared with patients with essential hypertension. Funding: None.